Implementasi Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar Pjok Pada Materi Bola Basket - Putra, I Putu Andika; Adi, I Putu Panca; Dartini, Ni Putu Dwi Sucita (STKIP AGAMA HINDU SINGARAJA, 2024)
This study aims to determine the improvement of learning outcomes (PJOK) through basketball material for Class X2 students of SMA Negeri 9 Denpasar by implementing the Problem Based Learning learning model. This research is a type of classroom action research. The subjects of this study were class X2 students of SMA Negeri 9 Denpasar, while the object of the study was basketball shooting and passing material with the implementation of the Problem Based Learning learning model. Data were taken by means of test observation of passing technique movements, shooting techniques, with the assessment format of passing techniques, shooting techniques, on cognitive and psychomotor aspects. Data were analyzed using Descriptive Statistics analysis. The results of the study showed that the implementation of the Problem Based Learning learning model can improve learning outcomes (PJOK) through basketball for Class X2 students of SMA Negeri 9 Denpasar in the 2023/2024 Academic Year. It can be seen in cycle I and cycle II that the percentage increase in PJOK learning outcomes is quite significant. So the results of PJOK learning in cycle I, the number of students who completed was 14 people and those who did not complete were 22 people. Meanwhile, in cycle II, the number of students who completed was 33 people and 3 people received average or sufficient scores.